Higher pre‐pregnancy body mass index is associated with excessive gestational weight gain in normal weight Chinese mothers with gestational diabetes. Issue 5 (19th January 2016) - Yang, Yue; Wei, Qiong; Yu, Hong; Wang, Pin; Xia, Wenqing; Huang, Rong; Cai, Rongrong; Sun, Haixia; Wang, Shaohua
Abstract: Aim: To assess how pre‐pregnancy body mass index (BMI) affects pregnancy outcome and total gestational weight gain (GWG) in a cohort of women with gestational diabetes (GDM). Methods: Pregnant women at 24–28 gestational weeks diagnosed with GDM were classified as normal weight (pre‐pregnancy BMI, 18.5–24.9 kg/m 2 ) or overweight (pre‐pregnancy BMI, 25.0–29.9 kg/m 2 ). GWG was derived from the self‐reported pre‐pregnancy and pre‐delivery weights, and analyzed using 2009 Institute of Medicine categories. Results: A total of 106 GDM women were categorized as normal weight ( n = 79) or overweight ( n = 27). No statistically significant differences were found between the groups in terms of various obstetrical and neonatal outcomes. Higher pre‐pregnancy BMI, however, was associated with excessive GWG during pregnancy (difference between groups, P = 0.013). Furthermore, pre‐pregnancy BMI (OR, 0.529; 95%CI: 0.377–0.742; P = 0.000) and pre‐pregnancy overweight (OR, 3.825; 95%CI: 1.469–9.959; P = 0.006) were independent factors of GWG. Conclusions: Among Chinese GDM women, overweight GDM mothers gain excessive weight during pregnancy. Regulation of pre‐pregnancy bodyweight might be an appropriate precaution against excessive GWG.